1993
DOI: 10.1002/pi.4990300113
|View full text |Cite
|
Sign up to set email alerts
|

Fractional composition of partly hydrolysed polyvinyl acetate and its compatibility with hydroxypropyl methylcellulose in aqueous solutions

Abstract: Fractionation of partly hydrolysed polyvinyl acetate (PVA) was performed by warming of its aqueous solutions. The following properties of the obtained fractions were determined: viscosity, molecular weight and molecular weight distribution, surface tension, and absorbance in the IR range. The blockiness of the polymer molecules, characterized by their behaviour towards iodine‐containing systems such as I2,‐H3BO3 and I2,‐KI, was estimated. Fractionation of the aqueous solutions of PVA by warming is based mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The final fractions are F3 and F4 respectively. [10] and with Lerner and Alon [16] these results, obtained by thermal cloud point fractionation, are a direct evidence that the fractionation is influenced simultaneously by the polydispersity in composition, molar mass and sequence distribution of the VAc monomer units.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The final fractions are F3 and F4 respectively. [10] and with Lerner and Alon [16] these results, obtained by thermal cloud point fractionation, are a direct evidence that the fractionation is influenced simultaneously by the polydispersity in composition, molar mass and sequence distribution of the VAc monomer units.…”
mentioning
confidence: 61%
“…For instance, Dawkins et al [9] have clearly demonstrated by reversed phase liquid chromatography, that commercial PVA samples with an average DH value of 72 mol% contain in fact PVA chains with DH values ranging from 65 to 85 mol%. Zilberman et al [10] came to a similar conclusion by cloud point fractionation, e.g., by temperature induced phase separation, of an aqueous PVA solution ( DH = 72.5 mol%). According to these authors it turned out that the average sequence distribution of vinyl acetate (VAc) and vinyl alcohol (VOH) monomer units, usually designated by "blockiness", has a major influence on the thermal phase separation and its compatibility with other water-soluble polymers.…”
Section: Introductionmentioning
confidence: 69%